Pediatric Dentist-Pediatrician Cooperation in Early Diagnosis of Congenital Tooth Agenesis - Akif Demirel; Şaziye Sarı (Galenos Yayinevi, 2019)
Early diagnosis of congenital tooth agenesis increases the quality of treatment options and the final success of the treatment. However, in some clinical conditions, overlooking this diagnosis causes late diagnosis of these anomalies. Late diagnosis reduces the number of appropriate treatments, increases the cost of treatment and may lead to possible complications. In the diagnosis of congenital tooth agenesis, findings during the routine medical examination of the pediatric patient are beneficial. At this point, as well as pediatric dentists, pediatricians also play a great role in early diagnosis of these anomalies. The aim of this study is to draw attention to pediatric dentist-pediatrician cooperation in the early diagnosis of congenital tooth agenesis.